Multi-Utilities : Policy - Promotion, Tolerance, or Control? - Sommer, Dirk (World Bank, Washington, DC, 2012)
Some utilities have responded to recent changes in technology and market liberalization by turning themselves into "multi-utilities" that bundle traditionally distinct services. A companion Note reviews recent trends in horizontal integration of utilities. This Note looks at the policy and regulatory implications of those trends for developing countries. The question facing policymakers is whether the emergence of multi-utilities should be encouraged as a means of improving access and quality of utility services -- or subjected to closer control to guard against potential dangers arising from less competition, greater regulatory complexity, and more concentrated political power in the utilities.